Beyond-CMOS Nanodevices 1 - Balestra, Francis (London : ISTE ; Hoboken, NJ : Wiley, 2014)
This book offers a comprehensive review of the state-of-the-art in innovative Beyond-CMOS nanodevices for developing novel functionalities, logic and memories dedicated to researchers, engineers and students. It particularly focuses on the interest of nanostructures and nanodevices (nanowires, small slope switches, 2D layers, nanostructured materials, etc.) for advanced More than Moore (RF-nanosensors-energy harvesters, on-chip electronic cooling, etc.) and Beyond-CMOS logic and memories applications.
Chapter 5. Portable, Integrated Lock-In-Amplifier-Based System For Real-Time Impedimetric Measurements On Nanowires Biosensors5.1. Introduction; 5.2. Portable stand-alone system; 5.3. Integrated impedimetric interface; 5.4. Impedimetric measurements on nanowire sensors; 5.5. Bibliography; Part 2. New Materials, Devices And Technologies For Energy Harvesting; Part 2. Introduction; Chapter 6. Vibrational Energy Harvesting; 6.1. Introduction; 6.2. Piezoelectric energy transducer; 6.2.1. Introduction; 6.2.2. State-of-the-art devices and materials.
6.2.3. MEMS piezoelectric vibration energy harvesting transducers.
Includes bibliographical references at the end of each chapters and index.
Print version record.
Keywords: Nanoelectronics; Nanostructures; Metal oxide semiconductors, Complementary; TECHNOLOGY & ENGINEERING -- Mechanical; Metal oxide semiconductors, Complementary; Nanoelectronics; Nanostructures; Electronic books